Gamma irradiation preserves the nutritional profile of wild Boletus edulis Bull.: Fr. - Fernandes, Ângela (2015)
Mushrooms contain about 90% water, which leads to a faster deterioration due to senescence, browning, water loss and microbial attack [1]. Wild species are characterized for their seasonality, demanding the application of suitable preservation technologies. Irradiation is recognized as a safe and effective method for conservation, being used worldwide to extend the shelf-life of raw foods [2]. The present work reports the effects of gamma irradiation on the chemical composition of Boletus edulis Bull.:Fr. wild samples. The fruiting bodies were collected in Trás-os-Montes (Northeast of Portugal) in November 2012. The irradiation was performed in experimental equipment with four 60Co sources, at 1 and 2 kGy. Proximate composition was evaluated by official procedures, fatty acids were analyzed by gas-chromatography coupled to flame ionization detection (GC-FID), while sugars and tocopherols were determined by high performance liquid chromatography (HPLC) coupled to refraction index (RI) and fluorescence detectors, respectively. The nutritional profiles (proximate composition) were not affected in high extension. Fatty acids and sugars were slightly affected, decreasing with increasing doses. On the other hand, there has been a preservation of tocopherols content with 1 kGy dose. Nevertheless, despite these detected differences, the results of nutritional parameters (the most relevant in terms of mushroom acceptability by consumers) were less affected. Gamma irradiation, up to the doses used in this work, might represent a useful technology for mushrooms conservation.